2012
DOI: 10.1097/scs.0b013e318266fd4c
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Mandible Bone by Treatment of Resected Bone With Pasteurization

Abstract: The results of long-term follow-up for reimplantation of the mandibular bone treated with pasteurization are reported. Mandibulectomy was performed for mandibular malignancy in 3 cases. The resected bones were subsequently reimplanted after treatment with pasteurization in 3 cases to eradicate tumor cells involved in the resected bone. Although postoperative infection was observed in 2 of 3 cases, reimplantation of the resected mandibular bone treated by pasteurization was finally successful. Ten to 22 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Favourable long-term clinical results have been observed with pasteurization of mandibular tumour-bearing bone 17 and other sources, such as pelvic grafts. 18 Pasteurized bone has been used for reconstruction after resection of malignant periacetabular tumours, 19 bone and soft tissue sarcomas, 20 and distal tibiae with 'en bloc' intra-articular excision and ankle arthrodesis.…”
mentioning
confidence: 92%
“…Favourable long-term clinical results have been observed with pasteurization of mandibular tumour-bearing bone 17 and other sources, such as pelvic grafts. 18 Pasteurized bone has been used for reconstruction after resection of malignant periacetabular tumours, 19 bone and soft tissue sarcomas, 20 and distal tibiae with 'en bloc' intra-articular excision and ankle arthrodesis.…”
mentioning
confidence: 92%
“…Recently, we showed that reimplantation of a pasteurized mandible yielded good results in terms of osteoinductive activity as well as tumor cell eradication. 7 This method appears to be suitable for immediate reimplantation. However, histologically high-risk cases concerning tumor recurrence might need secondary reconstruction as they wait for confirmation of no-recurrence status in the primary site.…”
mentioning
confidence: 96%